Historical development of medicaments in the treatment of dental disease - Pavlović Violeta; Živković Slavoljub (Serbian Medical Society - Dental Section, Belgrade, 2003)
The purpose of this study was to present the historical development of certain medicaments and point out their role in the treatment of teeth with pulpal and periapical disease. Some in particular, among numerous medicaments that were used throughout history, are still present today.